Dietary Tomato, but Not Lycopene Supplementation, Impacts Molecular Outcomes of Castration-resistant Prostate Cancer in the TRAMP Model (P05-015-19) - Applegate, Catherine (Curr Dev Nutr, 2019)
OBJECTIVES: The objective was to determine whether dietary tomato or lycopene supplementation impacted the expression of biomarkers associated with aggressive tumors and poorer prognostic outcomes in castration-resistant prostate cancer (CRPC). METHODS: Transgenic adenocarcinoma of the mouse prostate (TRAMP) mice were castrated at 12 weeks of age to mimic the effects of androgen deprivation therapy (ADT) leading to CRPC. Mice were separated into three dietary groups (n = 30/group) and fed powdered, modified AIN-93 G diets containing 10% tomato powder (TP), lycopene beadlets matched for lycopene content of TP (LYCO), or placebo beadlets (PLAC). Tumors were detected and monitored for growth by ultrasound scan. After 5 weeks of CRPC growth, mice were euthanized, and prostate and tumor tissues were collected. Histological analysis was used to identify presence of tumor neuroendocrine (NE) phenotype (by synaptophysin [syp] expression) and androgen receptor (AR) expression. ELISA and Western blot were used to quantify interleukin-6 (IL-6) and STAT3, and RT-PCR was used to measure downstream targets of both AR and STAT3. RESULTS: No differences were observed between AR expression or presence of the NE phenotype between dietary groups. However, lower tumor weight was associated with both AR and syp expression in mice fed TP. A positive correlation (P = 0.03) was observed between reduced tumor IL-6 (P = 0.012) and reduced phosphorylation (activation) of STAT3 (P = 0.017) in tumors of mice fed TP when compared to PLAC or LYCO. RNA analysis showed reduced expression of genes related to invasion (mmp-2; P = 0.006), cell proliferation (cdk1; P = 0.01), NE phenotype (ngfr; P = 0.001), and androgen metabolism (srd5a2; P = 0.03) in tumors of TP-fed mice. CONCLUSIONS: Physiological levels of dietary tomato, but not lycopene supplementation, reduced the expression of molecular biomarkers typically upregulated in CRPC tissues that are associated with tumor growth and metastasis. FUNDING SOURCES: This research is supported by the National Institute of Biomedical Imaging and Bioengineering of the National Institutes of Health.